(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND: The aim of this study is to introduce the uncommonly used Co-Plot method which is called the multivariate graphical analysis and to apply this method to a data set including tobacco control in European region. METHODS: This study uses the data from the World Health Organization database according to Human Development Index of European countries. It takes into account variables such as smoking prevalence in young people and adults, the proportion of smoking-related deaths and domestic legislations cases pertaining to tobacco products and analyses the data using the Co-Plot method. RESULTS: Results of the study demonstrated that smoking prevalence and restrictions on advertising of tobacco products were highly negatively correlated. The proportion of deaths associated with smoking-related diseases increased parallel to the increase in the smoking prevalence in young people and adults. Norway, France and Finland have enforced legal limitations on direct and indirect advertising, and thus there has been a decline in smoking prevalence among young people and adults. In some countries, including Ireland, Italy and Serbia, the prevalence of smoking among the young has decreased due to the new or increased legal restrictions on the sale distribution of tobacco products. The governments in the Czech Republic, Kazakhstan, Estonia, Croatia, the Netherlands, Belgium, and Poland have placed restrictions on direct and indirect advertising. The distribution of other causes-related deaths and lung cancer-related deaths are high. CONCLUSION: The restrictions on tobacco products were tightened in time with the increased prevalence of smoking and proportion of smoking-related deaths. It can be said that the significant relationships identified in this study have even more pertinence in developed countries. Consequently, Co-Plot method has enabled deeper data interpretations of the relationships between the countries and the variables in this study.